2013
DOI: 10.1111/1471-0528.12147
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of pregnancy after first‐trimester exposure to mifepristone: an observational prospective study

Abstract: Objective To report the follow-up of continuing pregnancies after first-trimester exposure to mifepristone.Design Observational prospective study.Setting France.Sample Patients exposed to mifepristone during the first 12 weeks of pregnancy.Methods Women were included in the study when they or their doctors asked a French pharmacovigilance centre or the Paris Teratogen Information Service about the risk of mifepristone exposure in early pregnancy. Exclusion criteria were requests received after 22 weeks of gest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 22 publications
1
13
0
1
Order By: Relevance
“…A recent prospective study from France reported on 46 pregnancies exposed to mifepristone only [28]. Two major malformations occurred among 38 continuing pregnancies (5.3%), which, based on these small numbers, does not appear to be significantly elevated above the expected proportion of about 3%.…”
Section: Discussionmentioning
confidence: 83%
“…A recent prospective study from France reported on 46 pregnancies exposed to mifepristone only [28]. Two major malformations occurred among 38 continuing pregnancies (5.3%), which, based on these small numbers, does not appear to be significantly elevated above the expected proportion of about 3%.…”
Section: Discussionmentioning
confidence: 83%
“…Hormone intake by the mother has not been described to have an influence on renal morphogenesis, which seems to be a self-regulating process involving complex molecular mechanisms and gene regulation during fetal life (21,22). In addition, a review of pregnancies after exposure to mifepristone (given to induce abortion) or UPA (given for emergency contraception), respectively, shows no additional risk of congenital anomalies (23,24). The baby showed no renal function anomaly and no signs of vesicoureteral reflux.…”
Section: Discussionmentioning
confidence: 99%
“…Most individuals with a continuing pregnancy opt to complete the abortion, but patients should be supported in their choice of how to proceed. No evidence exists to date of a teratogenic effect of mifepristone [34]. However, misoprostol can result in congenital anomalies, such as limb defects with or without Möbius' syndrome (ie, facial paralysis), when used during the first trimester [35][36][37][38][39].…”
Section: Teratogenicity and Ongoing Pregnancymentioning
confidence: 99%